Effect of Different Salinity on Growth and Survival of Mud Crab (Scylla serrata) - Erika Rahmi; Muhammad Marzuki; Rangga Idris Affandi (Journal of Fish Health, 2026)
Mud crab (Scylla serrata) is a group of crustaceans that live in mangrove and estuarine ecosystems. Mud crab have potential with high economic value and have a lot of interest from local and international communities because they have very high nutritional value. In cultivation activities, one of the factors that affect the growth and survival of mud crab is water quality. One of the most important water quality parameters in mud crab cultivation is salinity. Salinity is a water quality parameter that has a limiting factor on the metabolic and physiological conditions of mud crab. This study aims to determine the effect of different salinities on the growth and survival of mud crab (Scylla serrata). The method used in this study is an experimental method with a complete randomized design (CRD) consisting of 5 treatments and 3 replicates, namely P1: 5 g L-1, P2: 10 g L-1, P3: 15 g L-1, P4: 20 g L-1 and K (control): 28 g L-1. The results showed that the best mud crab growth was in the 15 g L-1 salinity treatment, the value obtained in absolute weight growth of 12.33 ± 4.93 g, the specific weight growth rate value of 0.28 ± 0.10%/day with a survival rate of 100%. It can be concluded that different salinity treatments have a significant effect on the growth and survival of mud crab.